Taking action : creating sustainable change in student affairs - Ewell, Sara B.; Giblin, Joan; McNabb, Joe (Emerald Publishing Limited : Information Age Publishing, Inc., 2023)
"Action Research can empower all administrators in higher education to engage more effectively in resolving challenges in colleges and universities. Scholar-practitioners are particularly well poised to impact three defined areas of practice: college students, faculty, and curriculum, teaching and learning. Through these three areas of foci broad issues within higher education are explored. Action Research is a powerful, localized methodology for impacting difficult and complex issues embedded in organizations. Higher education administrators regularly confront these types of difficult issues and hold the responsibility to solve these problems"-- Provided by publisher.
Keywords: Student affairs services -- United States.; College students -- Services for -- United States.; Action research in education -- United States.; Education -- Student Life & Student Affairs.; Extra-curricular activities.; Educational administration and organization.; Student life.; elektronické knihy; electronic books